2017
DOI: 10.26458/1734
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Consumers in Greece: Who Are They?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This step not only ensures compliance with halal standards but also reflects ethical business practices, which are increasingly valued by consumers (Ashraf, 2019;Indarti et al, 2020). Previous studies have indicated that consumer trust and loyalty are positively influenced by perceived ethical behavior of businesses (Delistavrou et al, 2017;Piligrimiene et al, 2020).…”
Section: Figure 3 Operations Process Transformationmentioning
confidence: 99%
“…This step not only ensures compliance with halal standards but also reflects ethical business practices, which are increasingly valued by consumers (Ashraf, 2019;Indarti et al, 2020). Previous studies have indicated that consumer trust and loyalty are positively influenced by perceived ethical behavior of businesses (Delistavrou et al, 2017;Piligrimiene et al, 2020).…”
Section: Figure 3 Operations Process Transformationmentioning
confidence: 99%